PENERTIBAN PEDAGANG KAKI LIMA OLEH SATUAN POLISI PAMONG PRAJA DI KOTA PARIAMAN - Satria M. Syamnoer (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2020)
This study aims to determine the process of controlling street vendors conducted by the Civil Service Police Unit in the City of Pariaman. How is the data collection on the street vendors, related to giving warnings to the street vendors who violated and the implementation of the regulation carried out by the Pariaman Municipal Civil Service Police Unit. This research uses descriptive qualitative research method with inductive approach. Data collection through interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation, data verification and triangulation. In this study needed data in the form of primary and secondary data obtained through field service and agencies. From this research it shows that the process of controlling street vendors in the City of Pariaman by the Civil Service Police Unit has not been carried out optimally. This is because the Pariaman City Civil Service Police Unit has not conducted data collection properly and the attitude of the street hawkers who disregarded reprimands and appeals from the rule enforcers but when carried out in order instead demanded justice and mercy. Keywords: control of street vendors